Perancangan Sistem Informasi Manajemen Pemesanan Paket Wisata Berbasis Web untuk Meningkatkan Efisiensi Operasional PT Nusa Mulya - Yudi alfajri; Nurjanah Darmi Putri; Nurcahaya Marbun; Roni Saputra; Januardi (LPPM Universitas Ekasakti, 2025)
This study aims to design and develop a web-based management information system for travel package reservations to enhance operational efficiency at PT Nusa Mulya. The background of this research stems from the company’s reliance on a manual booking process, which results in inefficiencies in customer service and data management. This research applies a Research and Development (R&D) method using the Waterfall software development model, consisting of requirement analysis, system design, implementation, and blackbox testing. The system was developed using PHP as the programming language and MySQL as the database management system, supported by XAMPP as the local server environment. Data collection techniques included direct observation, literature review, and documentation analysis from the company's internal operations. The results of the system development indicate that the web-based information system significantly accelerates the booking process, improves data accuracy, and supports managerial decision-making more effectively. With this system, PT Nusa Mulya can provide more responsive and technology-based services to its customers and strengthen its competitiveness in the digital tourism industry.